Robert Ludlum's the Blackbriar genesis [large type] - Gervais, Simon (Novelist); Ludlum, Robert, 1927-2001 (Gervais, Simon (Novelist). Blackbriar series, 2022)
The assassination of a Treadstone agent leads two Blackbriar operatives down a rabbit hole of deceit and betrayal in this explosive new series from the world of Robert Ludlum. A car explodes along a quiet Prague side street--among the dead is an undercover Treadstone agent. It's not unusual for such men to meet their fates on an operation, but in this case there's one catch. None of his superiors know what he was doing there. Two Blackbriar operatives, Helen Jouvert and Donovan Wade, are sent to investigate. Their search for answers will take them deeper into the world of conspiracy and fake news than they ever expected. Treadstone and Blackbriar may be two sides of the same coin, intelligence and counterintelligence, but they have one thing in common, answers can be the deadliest commodity of all.